Pengaruh Brand Experience dan Brand Image terhadap Brand Loyalty dengan Brand Trust sebagai Variabel Intervening - Riyanto, Fauzi Andhi (Politeknik Negeri Padang, 2023)
The purpose of this study was to determine the effect of Brand Experience and Brand Image on Brand Loyalty on Culinary Products Sate Kambing Mas in Kartasura with Brand Trust as an intervening variable in Solo Raya. The research method is explanatory research. In this study, the authors used a quantitative assessment method. This study uses a population of people in Solo Raya who have bought products at Sate Kambing